Persepsi Guru terhadap Pelaksanaan Kegiatan Kelompok Kerja Guru (KKG) SD Negeri di Kecamatan Palupuh Kabupaten Agam - Tesi Rahmadila Putri; Irsyad Irsyad; Jasrial Jasrial; Ahmad Sabandi (Journal of Educational Administration and Leadership, 2020)
This study aims to obtain information about Teachers' Perceptions of the Implementation of Public Elementary School Teacher Working Group (TWG) Activities in Palupuh Subdistrict, Agam Regency, as seen in terms of TWG facilities and infrastructure, TWG implementation time, material discussed in the TWG, resource persons TWG, motivation to participate in TWG activities, and the benefits of participating in TWG activities. The research questions asked, namely How Teachers' Perception of the Implementation of Public Elementary School Teacher Working Group (TWG) Activities in Palupuh District, Agam Regency, seen from the facilities and infrastructure needed in the TWG activities, the timing of the TWG activities, the material discussed in the TWG activities, teacher guides in TWG activities, teacher motivation in participating in TWG activities, and the benefits of participating in TWG activities.This type of research is descriptive research with quantitative research methods. The study population numbered 129 people with a sample of 38 people. This research used simple random sampling technique. The research instrument used was a questionnaire in the form of a Likert scale which had been tested for validity and reliability. The data is processed with the formula average (Mean). The results of the study as a whole show that the Teachers' Perception of the Implementation of Public SD Teachers Working Group (TWG) Activities in Palupuh District, Agam Regency is already in the good category with an average score of 4.22.